Free Vibrations of Liquid-Filled Cylindrical Shells Reinforced by a Cross System of Ribs under Axial Compression with Regard to Discrete Allocation of Ribs - F.S. Latifov; A.A. Aliyev (Механика машин, механизмов и материалов, 2009)
The paper is devoted to the investigation of vibrations of liquid-filled cylindrical shell reinforced by discretely distributed cross system of ribs under axial compression. It is assumed that the ribs are uniformly distributed on the surface of the shell. The problem is solved by energetic method. Using the Hamilton-Ostrogradsky principle, the frequency equation is constructed and its least root is found. Influence of the parameters of external medium and contractive force on the parameters of eager vibrations of the system is analyzed.